Association between unintentional firearm injury characteristics and deaths in adolescents - Ashley A. Hollo; Mairead Dillon; Jennifer A. Hoffmann; Ashley Blanchard; Maya Haasz (BMC, 2024)
Abstract Background Approximately 15% of pediatric firearm injuries are unintentional. While demographic characteristics of unintentional firearm injuries have been described, the relationship between injury characteristics and mortality is not well understood. In this study, we identified injury characteristics associated with fatality among unintentional firearm injuries in adolescents. Methods We conducted a retrospective (May 2022-May 2023) cross-sectional study of unintentional firearm injuries among adolescents 12-17 years old using the Gun Violence Archive. Variables included victim age and sex, shooter age and sex, injury location, injury circumstance, number of firearms, type of firearm, firearm owner, census region, and shooter relationship to the victim. Logistic regression was used to identify variables associated with fatality. Results Of 319 unintentional incidents, 212 (66.5%) were non-fatal and 107 (34.5%) were fatal. Of all shootings, 176 (55.2%) occurred in a residence. A shooter was identified in 256 (80.3%) cases; 43.0% of these were a peer of the victim. The adjusted odds of fatality were higher when a peer was the shooter (aOR 5.38, 95% CI 2.57, 11.80) compared to self-inflicted injury and when the shooting took place in the victim's residence (aOR 2.87, 95% CI 1.07, 7.88) or another residence (aOR 3.03, 95% CI 1.45, 6.67) versus a public location (Fig. 1). Conclusions Unintentional firearm injuries were more likely fatal when a peer was the shooter and when the shooting occurred at a residence. This amplifies the importance of safe home firearm storage and exploring other evidence-based approaches to decreasing youth access to firearms.